Fraud detection and forensic accounting - (:unkn) unknown (Springer-Verlag Berlin Heidelberg, 2012)
A quick search for the meaning of fraud in the dictionary states that fraud is deceit, impersonation with intent to deceive, criminal deception done with the intention of gaining an advantage. The Institute of Turkish History explains the word fraud as a deceptive trick, scam, game, artifice, cabal which is committed to cheat, mislead someone and contributing something useless to something in order to gain advantage (Institute of Turkish History 1998, p 995). According to another definition, fraud is to create a misjudgment or maintain an existing misjudgment to induce somebody to make a contract (Arzova 2003, p 118). Another definition says it is to enrich oneself by intentionally reducing the value/worth of an asset in secret. © 2012 Springer-Verlag Berlin Heidelberg. All rights are reserved.